NALISIS PENGARUH KOMPETENSI, PELATIHAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA TIM TANGGAP DARURAT FIRE AND EMERGENCY SERVICES DI WILAYAH KERJA TAMBANG PT VALE IND Tbk - Made Galuh Ginanti; Mahlia Muis; Maat Pono (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2018)
Human role as a resource in the organization is increasingly believed in its importance, thus increasingly encouraging the development of knowledge about how to utilize human resources in order to achieve optimal conditions. This study aims to determine the influence of competence, training and compensation jointly and partially to Job Satisfaction. In addition, we also jointly examine the influence of competence, training and compensation on the performance of Fire and Emergency Services employees of PT VALE Indonesia, Tbk. This study was conducted by taking as many as 55 respondents who also used as sample research with the distribution of respondents by age, last education level, gender, position in the job. Data collection is done through interview technique in the beginning of data collection and questionnaires or questionnaires distributed to the respondents used as data in data processing research. Data were analyzed by using Path Analysis (Path Analysis). The result of the research shows that the competence variable has a direct and significant effect on the performance of Fire and Emergency Services employees of PT VALE Ind, Tbk with coefficient value of 0,397. Training and compensation have direct and positive impact on job satisfaction with coefficient value of 0,325 and 0,494. Based on the result of the research, it can be concluded that there are some other factors that influence the variable of job satisfaction and employee performance, but not described in this case.